ANALYSIS OF FARMING NILAM (POGOSTEMON CABLIN BENTH) AT TOARI DISTRICT OF KOLAKA - Bustanil Yusuf; Kabul Budiman; Nursalam Nursalam (Agribusiness Journal, 2016)
This research aims to; 1) determine the factors that affect the production of patchouli production, 2) determine the allocative efficiency of production factors patchouli farming, 3) determine the scale of business, 4) To determine the financial feasibility of farming patchouli. The sample in this study is a research location patchouli farmers totaling 50 respondents. Data were analyzed using Cobb-Douglass, Statistics Test Analysis, analysis of allocative efficiency, scale of operations and financial feasibility. This study shows that: 1) The results of the analysis test F known that simultaneously all variables significant impact significantly on the production, t test results showed that the only variable land area, insecticides, and plant spacing real impact significantly on production, while seeds and fertilizers (Urea and NPK), pesticides (herbicides and fungicides), labor and parts not significant 2) from the analysis of allocative efficiency is obtained that the widespread use of land and insecticides have not been efficient, from the economic aspect adding the proportion of these variables can still be done to maximize profits , while the seeds, fertilizers (Urea and NPK), pesticides (herbicides and fungicides) and labor efficient, 3) The results of the analysis of the business scale is known that farming patchouli in District Toari under conditions of increasing returns to scale means that they do increase production factor physically to maximize production, 4) The results of a financial analysis proves that farming patchouli in District Toari provide benefits for a total of land area of 37.9 hectares, obtained acceptance of Rp 674.1 million, with a total cost of USD 310 048 508, in order to obtain net income of Rp 340 130 475, while the value of NBCR 1.17, 51.77659 million NPV, IRR of 26.3%, average BEP Revenue USD 713 393, average BEP Production of 102kg, and average BEP Price Rp 3,376/kg.